Reasons Why Infants Between the Ages of Seven and Twelve Months Do Not Receive Exclusive Breastfeeding - Mareza Yolanda Umar; Psiari Kusuma Wardani; Abdullah (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2026)
Exclusive breastfeeding during the first six months of life is essential for infant growth, immunity, and neonatal health. However, exclusive breastfeeding coverage remains suboptimal and is influenced by maternal and environmental factors. This study aimed to analyze determinants associated with the failure of exclusive breastfeeding among infants aged 7–12 months in Pesawaran Regency, Lampung Province, Indonesia. A cross-sectional study was conducted from May to June 2025 in five subdistricts with low breastfeeding coverage. The sample consisted of 343 mothers selected using stratified random sampling. Data were analyzed using chi-square tests and multiple logistic regression at a significance level of p < 0.05. Bivariate analysis showed that age, occupation, education, parity, knowledge, attitude, family support, and health worker support were significantly associated with exclusive breastfeeding (p < 0.05). Multivariate analysis indicated that age (OR=1.937), occupation (OR=0.521), education (OR=0.530), knowledge (OR=1.755), attitude (OR=2.192), and family support (OR=0.575) significantly influenced exclusive breastfeeding. Maternal attitude was the strongest predictor. Strengthening breastfeeding education, workplace lactation support, and family involvement is recommended to improve exclusive breastfeeding coverage.